Improving Students’ Speaking Skill by Using Guessing Game at Grade VIII A of SMP Negeri 1 Tanjung Pinang - Nirwaty Nirwaty (J-SHMIC : Journal of English for Academic, 2020)
Students’ motivation in learning English as a Foreign language might be influenced by strategies used in the classroom. This article aims to find out to what extend guessing game improve students’ speaking skill and to find out the factors influence the students’ speaking skill. This is action research which the samples were taken from VIII A class consisted on 32 students at SMPN 1 Tanjungpinang. The instruments in this research were using test and observation.